Economic impacts assessment of pleuropneumonia burden and control in pastoral cattle herds of North-central Nigeria (2017)
Contagious bovine pleuropneumonia (CBPP) is a trans-boundary infectious and contagious respiratory disease of cattle caused by Mycoplasma mycoides subsp. mycoides. It is a disease of high economic importance because of its ability to compromise food security. Information on its economic burden in pastoral cattle herds of Niger State, North-central Nigeria is not readily available. This study was aimed at investigating the economic impacts of CBPP to pastoralists in Niger State, North-central Nigeria, by determining its burden, returns to investments in its control, and cost-effectiveness of the control interventions ex-post evaluation, to provide baseline estimates that will assist animal health authorities and international donors in making investment decisions on its control in Nigeria. A questionnaire-based cross sectional study was conducted in 125 pastoral cattle herds. Economic analyses were conducted using total economic cost, benefit-cost analysis and cost-effectiveness analysis models. The values of mortality and morbidity losses to the herders were 219,038.5 USD and 35,598.8 USD, respectively. The total economic cost of CBPP to pastoralists was estimated to be 294,800.3 USD. Return on investment in CBPP control by vaccination and treatment was positive, with a benefit-cost ratio of 6.4. The Average cost-effectiveness ratio value for treatment intervention was 13.7 USD per life cattle saved and for vaccination option was 0.6 USD per death/cull averted. The estimated economic costs due to CBPP have shown that the disease was of high economic importance and must be controlled.